2019
DOI: 10.1073/pnas.1909298116
|View full text |Cite
|
Sign up to set email alerts
|

How the phage T4 injection machinery works including energetics, forces, and dynamic pathway

Abstract: The virus bacteriophage T4, from the family Myoviridae, employs an intriguing contractile injection machine to inject its genome into the bacterium Escherichia coli. Although the atomic structure of phage T4 is largely understood, the dynamics of its injection machinery remains unknown. This study contributes a system-level model describing the nonlinear dynamics of the phage T4 injection machinery interacting with a host cell. The model employs a continuum representation of the contractile sheath using elasti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 32 publications
1
23
0
Order By: Relevance
“…Phage T4 has a tail that functions as a contractile nanomachine, with a rigid inner tail tube housed within a compressible outer sheath. When the phage is triggered to contract, the outer sheath compresses so that most of the baseplate structure moves and ∼40 nm of the inner tube is exposed [35][36][37]. Biophysical analysis of analogous contractile systems [38] and theoretical calculations are consistent with the assumption that the contractile force generated through the compression of the outer sleeve is sufficient to power the tail tube through the outer membrane [37].…”
Section: Phage Tails As Cell Puncturing Devicessupporting
confidence: 53%
“…Phage T4 has a tail that functions as a contractile nanomachine, with a rigid inner tail tube housed within a compressible outer sheath. When the phage is triggered to contract, the outer sheath compresses so that most of the baseplate structure moves and ∼40 nm of the inner tube is exposed [35][36][37]. Biophysical analysis of analogous contractile systems [38] and theoretical calculations are consistent with the assumption that the contractile force generated through the compression of the outer sleeve is sufficient to power the tail tube through the outer membrane [37].…”
Section: Phage Tails As Cell Puncturing Devicessupporting
confidence: 53%
“…Recently, a computational approach that modeled the T4 sheath using Kirchhoff's rod theory with parameters derived from molecular dynamics (MD) simulations of a short fragment of the sheath has been presented (23). The elastic body calculations were parametrized showing the main components and size of the pyocin particle free in solution (extended sheath) and attached to the cell surface (contracted sheath).…”
Section: Introductionmentioning
confidence: 99%
“…(D) Structure of a six-layer fragment of the pyocin sheath in the contracted state (5) to match the enthalpy of T4 sheath contraction (19) and the contraction time scale of the T6SS (20). Contraction was predicted to proceed via a rapid rotation of sheath subunits before their translation (23,24). Such a sequence of events is incompatible with maintaining the integrity of the sheath subunit, which was implied but not validated in the approach.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that about 96% of phages are double-stranded DNA genomes with tailed morphology, belonging to the order of Caudovirales [35]. Based on the tail structure, the Caudovirales order can be categorized into three families: Myoviridae (phages with a contractile tail, such as T4-like phages), Siphoviridae (phages with a non-contractile long tail, such as T5-like phages), and Podoviridae (phages with a short tail, such as T7-like phages) [36][37][38].…”
Section: Phages Infect Bacterial Biofilmsmentioning
confidence: 99%